Corporate diversification and the value of individual firms: A Bayesian approach - Mackey, Tyson B.; Barney, Jay B.; Dotson, Jeffrey P. (Strategic Management Journal, 2017)
Research summary: Prior theory suggests that the performance effects of a firm's diversification strategy depend on a firm's individual resources and capabilities and the setting within which it is operating. However, prior tests of this theory have examined the average diversification‐performance relationship across all firms, instead of estimating the diversification‐performance relationship at the individual firm level. Efforts to estimate this average relationship are inconsistent with a central assumption of much of strategic management theory—that firms maximize value by choosing strategies that exploit their heterogeneous resources and individual situation. By adopting an approach that allows an evaluation of the diversification‐performance relationship for individual firms, this article shows that firms, both focused and diversified, tend to choose that diversification strategy—focus, related diversification, or unrelated diversification—that maximizes value . Managerial summary: Instead of a universal diversification discount or premium, this article shows that the effect of diversification on performance is heterogeneously distributed across firms and that firms tend to be rational in their diversification decisions . Copyright © 2015 John Wiley & Sons, Ltd.